THE DIFFERENCES AMONG GENDER IN SPEAKING ANXIETY OF ENGLISH STUDENTS AT UNIVERSITY OF ISLAM MALANG - Faradisah Amelia (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Speaking is one of central elements of communication in EFL (English as a Foreign Language), it is an aspect that needs special attention and instruction. speaking is much to be used in communication. Feelings of anxiety is one of problems in speaking mastery from students learning process. The study aimed to check whether there is a gender difference in a speaking anxiety. Whether there is or not difference between gender in speaking anxiety of English Language was examined deeply in this study. The design of this research was used a quantitative descriptive design to collect the data related to learning objectives. The researcher took 30 participants from the fourth semester of University of Islam Malang. The procedure of the research applies by Google Form or questionnaire which sent to the class concerned. To analyses the data, the researcher used SPSS version 20. The results of this research showed that male students have a higher level of foreign language anxiety in speaking than female students. There was no significance difference level of foreign language anxiety between female and male students. They only have a little bit difference based on analyzed data used independent sample t-test in SPSS software.keywords: Speaking, anxiety, speaking anxiety, foreign language, gender